Settling behavior of microplastic hetero-aggregates in aquatic environments with varying salinity - Min Li; Jing Ou; Zhihe Chen (International Journal of Sediment Research)
The aggregation of microplastics (MPs) with sediments in natural water plays a crucial role in the general deposition and transport of plastic particles. However, the effect of salinity changes on the settling behavior of aggregates remains unclear. In this study, the aggregation and settling processes of sediment particles with spherical MPs were investigated using a settling tube and a microphotography device, in deionized water (pH 8.0) with 10–35 practical salinity units (PSU). Two-particle and three-particle aggregates were most commonly observed in the experiments. Increasing the salinity promoted the aggregation of MPs, reaching the largest average particle size at 25 PSU, but the mean Corey shape factor values exhibited minimal variations at different salinities. Meanwhile, the settling velocity of the aggregates was directly proportional to their particle size, and thus the average settling velocity also reached a maximum at 25 PSU. Although the settling velocity can be predicted with high correlation coefficients using existing formulas developed for static conditions, dynamic flow may reduce the settling velocity of aggregates and cause overestimation. Herein, a reduction coefficient was used to revise the settling velocity formula and predict the measured values with higher accuracy. This study provides insights into the aggregation and settlement of MPs in estuarine environments with varying salinity, which affect the fate and distribution of plastic particles in natural waters.